Revisited Reference Solar Proton Event of 23 February 1956: Assessment of the Cosmogenic‐Isotope Method Sensitivity to Extreme Solar Events - Usoskin, Ilya G.; Koldobskiy, Sergey A.; Kovaltsov, Gennady A.; Rozanov, Eugene V.; Sukhodolov, Timofei V.; Mishev, Alexander L.; Mironova, Irina A. (Journal of geophysical research. Space physics, 2020)
Our direct knowledge of solar eruptive events is limited to several decades and does not include extreme events, which can only be studied by the indirect proxy method over millennia, or by a large number of Sun‐like stars. There is a gap, spanning 1–2 orders of magnitude, in the strength of events between directly observed and reconstructed ones. Here, we study the proxy method sensitivity to identify extreme solar particle events (SPEs). First, the strongest directly observed SPE (23 February 1956), used as a reference for proxy‐based reconstructions, was revisited using the newly developed method. Next, sensitivity of the cosmogenic‐isotope method to detect a reference SPE was assessed against the precision and number of individual isotopic records, showing that it is too weak by a factor ≈30 to be reliably identified in a single record. Uncertainties of 10Be and 14C data are shown to be dominated by local/regional patterns and measurement errors, respectively. By combining several proxy records, a SPE 4–5 times stronger than the reference one can be potentially detected, increasing the present‐day sensitivity by an order of magnitude. This will allow filling the observational gap in SPE strength distribution, thus enriching statistics of extreme events from 3–4 presently known ones to several tens. This will provide a solid basis for research in the field of extreme events, both for fundamental science, namely solar and stellar physics, and practical applications, such as the risk assessments of severe space‐based hazards for modern technological society. Key Points The integral energy spectrum of the strongest directly observed SEP event of 23 February 1956 is revised Sensitivity of the cosmogenic‐isotope proxy method to extreme SEP events is assessed It is shown that the sensitivity of the proxy method can be significantly improved by a multiproxy approach